Design, synthesis and biological evaluation of novel pyrimidinedione derivatives as DPP-4 inhibitors. Issue 12 (1st July 2018) - Li, Ning; Wang, Li-Jun; Jiang, Bo; Guo, Shu-Ju; Li, Xiang-Qian; Chen, Xue-Chun; Luo, Jiao; Li, Chao; Wang, Yi; Shi, Da-Yong
Graphical abstract: Highlights: Pyrimidinedione derivatives were synthesized. SARs and molecular simulation studies were conducted. Compound 11 (IC50  = 64.47 nM) showed excellent inhibition of DPP-4. Compound 11 was potent in vivo hypoglycemic effect. Abstract: A series of novel pyrimidinedione derivatives were designed and evaluated for in vitro dipeptidyl peptidase-4 (DPP-4) inhibitory activity and in vivo anti-hyperglycemic efficacy. Among them, the representative compounds 11, 15 and 16 showed excellent inhibitory activity of DPP-4 with IC50 values of 64.47 nM, 188.7 nM and 65.36 nM, respectively. Further studies revealed that compound 11 was potent in vivo hypoglycemic effect. The structure–activity relationships of these pyrimidinedione derivatives had been discussed, which would be useful for developing novel DPP-4 inhibitors as treating type 2 diabetes.